so sánh A=\(\frac{8^{13}+1}{8^{14}+1}\)và B=\(\frac{8^{14+1}}{8^{15}+1}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\dfrac{7}{12}< \dfrac{7+1}{12+1}< \dfrac{78}{13}\Rightarrow\dfrac{7}{12}< \dfrac{8}{13}\)
b) \(-4,25=-\dfrac{425}{100}=-\dfrac{17}{4}=-\dfrac{34}{8}< -\dfrac{28}{8}\Rightarrow-4,25< -\dfrac{28}{8}\)
c) \(-0,33>-0,5=-\dfrac{1}{2}=-\dfrac{19}{38}\Rightarrow-0,33>-\dfrac{19}{38}\)
d) \(\dfrac{11}{13}< \dfrac{11+2}{13+2}=\dfrac{13}{15}\Rightarrow\dfrac{11}{13}< \dfrac{13}{15}\Rightarrow-\dfrac{11}{13}>-\dfrac{13}{15}\)
Bài 1:
a: -8/12<0<-3/-4
b: -56/24<0<7/3
c: 4/25<1<15/13
=>-4/25>-15/13
Bài 2:
a: =-60/45=-4/3
b: =4/15-3/2-8/5=8/30-45/30-48/30=-85/30=-17/6
Ta có
\(C=\frac{1}{2.3}+\frac{1}{3.4}+\frac{1}{4.5}...+\frac{1}{17.18}>A=\frac{1}{2.3}+\frac{1}{5.4}+...+\frac{1}{18.19}\)
\(C< =>\frac{3-2}{2.3}+\frac{4-3}{3.4}+\frac{5-4}{4.5}+...+\frac{18-17}{17.18}\)\(>A\)
\(C< =>\frac{1}{2}-\frac{1}{18}\)\(>A\)
\(C< =>\frac{4}{9}\)\(>A\left(1\right)\)
Lại có \(C=\frac{4}{9}< \frac{9}{19}=B\left(2\right)\)
Từ (1),(2) => B>A
\(A=\frac{15^8-1+3}{15^8-1}=1+\frac{3}{15^8-1}\)
\(B=\frac{15^8-3+3}{15^8-3}=1+\frac{3}{15^8-3}\)
Ta có: \(15^8-3< 15^8-1\)
=> B>A
A=B nha